Health evaluation of donkeys: parasite control methods and a model for challenge infections - Molento, Marcelo Beltrão; Vilela, Vinicius Longo Ribeiro (Brazilian Journal of Veterinary Research and Animal Science, 2021)
Donkeys, mules, and asses are domestic animals of worldwide distribution, found in all regions of Brazil. Although more health data is needed from these species, some sectors of today’s society are exploring alternatives to use these animals for milk production and the use of donkeys in social events and onotherapy. Donkeys (Equus asinus) are used in many everyday activities, but the animals need better welfare conditions. Although it is well known that endoparasite infections (i.e. cyathostomins, Strongylus spp., Parascaris sp.) can harm the clinical condition of the animals, there are limited clinical and laboratory supporting data, including registered therapeutic drugs for their control. The objective of the present work was to review the existing literature about parasite infections of donkeys, including their clinical implications, and the drug efficacy test to help practitioners improve their health management programs. To assist with that, we have developed a questionnaire to identify the risk factors of donkey farming, which is presented here in English and in Portuguese. Lastly, the present article also includes an original simulation using the susceptible-infected-recovered (SIR) model with low, moderate, and severe scenarios to help visualize the risk of parasite infections. The SIR model was based on the disease condition of donkeys in Brazil, using transient interaction levels from 0.0015 to 0.0025, infectivity levels from 0.10 to 0.40, and distinct recovery rates (R) from 0.01 to 0.08. As milk production is an expanding new activity worldwide, we want to emphasize that the first comprehensive studies must take into account differences in animal age, breed, and body condition score, local climate, pasture quality, day of sampling, and the period of lactation within the lactation curve to measure the health condition of donkeys. These data are considered important and will then be correlated to the parasite egg/oocyst (EPG or OoPG) counts in the feces using coproparasitological protocols (McMaster and Mini-FLOTAC), and even DNA-based techniques, to establish a novel data bank for donkeys. Target selective treatment has been proposed to be used as a routine in horses and will also be implemented in donkeys. This technique aims to reduce the number of anthelmintic treatments and, consequently, lessen parasite selection for resistance. The dynamic variations found by the SIR model are discussed in the text and should be taken into account when deciding the best health management implementation and parasite control programs. We think that more studies are needed to evaluate the basic physiological performance of donkeys in tropical areas to better understand their thermal adaptation, assuming that the animals are kept under acceptable clinical, nutritional, and housing conditions to express their resilient behavior. Cases of neglect and ill-treatment of animals must also be studied in infected conditions as well as their negative impacts. These strategies reinforce the concept of holistic farming with the possibility to improve specific informations, thereby improving the welfare of the donkeys.